Droplet Impingement into a Liquid Film; Numerical Study of Surface Tension Effect on the Crown Formation - Zamani Asl, Mohammad Mehdi; Dastyar, Zahra (European Journal of Computational Mechanics, 2022)
An axisymmetric numerical model is conducted to study the droplet impingement into a liquid film and crown formation. Through numerical modeling and experimental validation, the effect of different parameters such as surface tension, Weber number, and film thickness on crown evolution is investigated. Surfactant is added to water, aiming reduction of the surface tension in the surfactant-water mix. It was shown that the crown rim diameter increases with Weber in both water and surfactant-water mixture cases. Likewise, crown rim diameter increases with the film thickness in both different cases of fluids. Additionally, results revealed that surface tension does not affect the crown rim diameter. Nevertheless, crown height increases as surface tension decreases. At low values of surface tension, secondary droplets and the de-wetting region appear. These outcomes can be attributed to the domination of kinetic energy of crown rims in cases with low surface tensions.